Pengelolaan Sampah Di Kawasan Permukiman Kumuh Bantaran Sungai Perkotaan - Wahyu Saputra; Bianto Bianto (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2025)
Urban slum settlements that have developed along riverbanks face complex challenges related to waste management, which directly affect environmental quality and public health. Limited infrastructure, inadequate waste collection services, and community behaviors that do not yet support sustainable waste management are the main factors contributing to increased river pollution in these areas. This study aims to comprehensively examine the concepts, challenges, and strategies of waste management in urban riverbank slum settlements based on findings from previous studies. The method employed is a literature review, involving the analysis of relevant scientific articles, policy reports, and official documents at both national and international levels. The results indicate that waste management problems in riverbank areas are generally influenced by unequal access to waste services, weak policy enforcement, and limited community participation. Strategies commonly recommended in the literature include strengthening community-based waste management systems, improving infrastructure and waste services, integrating slum upgrading policies, and promoting sustainable environmental education. This review is expected to serve as a conceptual reference for policymaking and planning more effective and sustainable waste management in urban riverbank slum areas.